Avaliação da influência de eletrodos e gases de proteção em juntas soldadas do aço LNE 600 - Zanin, Henrique Soares (2023)
This work evaluated the behavior of high-strength, low-alloy steels (ARBL) after welding, due to the change in the mechanical properties of the material when subjected to this process. Therefore, the main objectives were to evaluate: the influence of different electrodes on tensile strength; the behavior of hardness in the thermally affected zone, the influence that the electrode and protective gases have on the microstructure, the ZTA size and the fatigue resistance of ARBL steels welded by the GMAW process, applied to components. To prepare the samples, three different types of electrodes were used: ER70S-6, ER110S-G and ER120S-G and two types of gases Ar + 5% O2 and Ar + 15% CO2, using LNE600 steel as the base material. During welding, the voltage and current parameters were kept constant according to the welding procedure specification. The results of the tensile and microhardness tests concluded that welding using the ER120S-G electrode in combination with Ar + 15% CO2, presented the best behavior with an average yield stress of 680 MPa and average hardness of 320 HV in the region of filler metal, the load used in the microhardness test was 0.2 Kgf. In microhardness there was no statistically significant difference for the coarse grain and refined grain regions. In high load and low cycle fatigue tests, the ER120S-G electrode combined with Ar + 5% O2 presented the highest average with 162 thousand cycles with 60% of the stipulated static load, other combinations presented cycle averages varying from 74 to 99 thousand being statistically equal. For the condition with a load of 50% of the design stipulation, only the combination of the ER70S-6 electrode with the O2 gas presented a lower performance than the others with 93 thousand cycles, the other combinations presented cycles between 175 and 189 thousand, being statistically equal.